GREEN ECONOMY IMPLEMENTATION STRATEGY FOR MSMEs IN ACEH BESAR TO ENCOURAGE SUSTAINABLE ECONOMIC DEVELOPMENT - Saiful Bahgia; Sari Yulis Terfiadi; Hamdani; Hasbi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The Sustainable Development Goals (SDGs) are a global agenda consisting of 17 main goals and 169 targets that cover social, economic, and environmental dimensions simultaneously. Overall, many MSMEs still implement conventional and non-environmentally friendly business practices. This study aims to identify suitable strategies for MSMEs in implementing the green economy concept and the impact on sustainable economic development in Aceh Besar Regency. This research is a field research, with a quantitative approach. The research sample amounted to 50 MSMEs consisting of 30 culinary sectors (70%) and 20 artisan sectors (30%). Data collection techniques through questionnaires, interviews and direct observation of MSMEs. Data analysis through quantitative methods with a SWOT analysis approach and Internal Factor Analysis (IFAS) and External Factor Analysis (EFAS) to formulate suitable strategies for MSMEs. The results of the study show that the IFAS analysis obtained a result of 3.8 as (X) and the EFAS analysis obtained a result of 3.4 as (Y), after obtaining these results, an alternative aggressive strategy (SO) was obtained in implementing the concept of green economy and sustainable economic development in Aceh Besar Regency. So that MSMEs currently have the potential of resources, management and products in utilizing cooperation opportunities to maximize marketing, knowledge and environmental awareness as well as regulatory support from the local government. Therefore, the results of this study can be used as a theoretical basis in the preparation of strategic policies by the government. The follow-up suggestions from the results of this study are in the form of a participatory approach as an approach that aims to be able to develop the capacity of MSMEs through training, workshops and technical guidance in the context of implementing a green economy in Aceh Besar Regency based on the phases that have been put forward in this study.